1983
DOI: 10.1007/bf02381460
|View full text |Cite
|
Sign up to set email alerts
|

Self-aggression in macaques: Five case studies

Abstract: ABSTRACT. Spontaneous self-aggressive behaviors Were observed in five adult male rhesus monkeys (Macaca mulatta) housed at a university facility..all were individually caged, were free of intercurrent disease, and were being utilized in ongoing research studies. The self-aggressive behaviors observed included self-biting, self-clasping, self-slapping, self-rubbing and threatening of body parts. In several cases, wounds were inflicted and medical treatment was required due to the severity of the lesions. A revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1984
1984
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…Reinhardt and Rossell, 2001) it nevertheless appears to be more common in singly-housed individuals and those that experienced socially restricted development Chamove, 1980, 1985;Brent et al, 1989b;Chamove et al, 1984;Gluck and Sackett, 1974;Pond and Rush, 1983;Reinhardt and Rossell, 2001;Woolverton et al, 1989). Furthermore this behaviour can be accentuated by a number of conditions including frustration (Gluck and Sackett, 1974), self-reward (Anderson and Chamove, 1980), excessive management disturbance , withdrawal of enrichment (Bryant et al, 1988;Chamove et al, 1984), tension or anxiety related to human presence (Pond and Rush, 1983;Skyner et al, 2004) and social contexts (Anderson and Chamove, 1980;Erwin et al, 1973). It has been suggested that it arises as the result of the absence of 'appropriate social aggression targets' during development when young animals would otherwise be involved in play-fighting (Anderson and Chamove, 1980), of self-stimulation when in an otherwise unstimulating environment , or of the development of a coping strategy to reduce arousal in distressing situations (Novak, 2003).…”
Section: Aggression and Social/solitary Housing Conditionsmentioning
confidence: 94%
See 2 more Smart Citations
“…Reinhardt and Rossell, 2001) it nevertheless appears to be more common in singly-housed individuals and those that experienced socially restricted development Chamove, 1980, 1985;Brent et al, 1989b;Chamove et al, 1984;Gluck and Sackett, 1974;Pond and Rush, 1983;Reinhardt and Rossell, 2001;Woolverton et al, 1989). Furthermore this behaviour can be accentuated by a number of conditions including frustration (Gluck and Sackett, 1974), self-reward (Anderson and Chamove, 1980), excessive management disturbance , withdrawal of enrichment (Bryant et al, 1988;Chamove et al, 1984), tension or anxiety related to human presence (Pond and Rush, 1983;Skyner et al, 2004) and social contexts (Anderson and Chamove, 1980;Erwin et al, 1973). It has been suggested that it arises as the result of the absence of 'appropriate social aggression targets' during development when young animals would otherwise be involved in play-fighting (Anderson and Chamove, 1980), of self-stimulation when in an otherwise unstimulating environment , or of the development of a coping strategy to reduce arousal in distressing situations (Novak, 2003).…”
Section: Aggression and Social/solitary Housing Conditionsmentioning
confidence: 94%
“…Anderson and Chamove (1980) describe self-aggression as behaviour that is 'abnormally frequent and/or intense threats or physical attacks directed towards one's own body which may or may not result in tissue damage' and while the causes of this behaviour remain unclear (see e.g. Reinhardt and Rossell, 2001) it nevertheless appears to be more common in singly-housed individuals and those that experienced socially restricted development Chamove, 1980, 1985;Brent et al, 1989b;Chamove et al, 1984;Gluck and Sackett, 1974;Pond and Rush, 1983;Reinhardt and Rossell, 2001;Woolverton et al, 1989). Furthermore this behaviour can be accentuated by a number of conditions including frustration (Gluck and Sackett, 1974), self-reward (Anderson and Chamove, 1980), excessive management disturbance , withdrawal of enrichment (Bryant et al, 1988;Chamove et al, 1984), tension or anxiety related to human presence (Pond and Rush, 1983;Skyner et al, 2004) and social contexts (Anderson and Chamove, 1980;Erwin et al, 1973).…”
Section: Aggression and Social/solitary Housing Conditionsmentioning
confidence: 96%
See 1 more Smart Citation
“…Spontaneous self-aggression including extensive biting of the upper limbs has also developed in housed Macaques experiencing stress (Pond, 1983). Both of our patients related fingernail biting, which progressed to severe mutilation, to anxiety and depression.…”
Section: Discussionmentioning
confidence: 56%
“…The following conditions are reported to increase SA: frustration (GLUCK & SACI,:ETT, 1974), sexual arousal (MAPLE, ERWIN & MITCHELL, 1974), ovarian hormonal state (BIELERT & HOWARD-TRIPP, 1983), pain (LEVINE et al, 1970) and threatening stimuli (ALLYN, DEYME & BEGUE, 1976;CHAMOVE & HARLOW, 1970;CROSS & HARLOW, 1965;POND & RUSH, 1983), but whether or not SA, social aggression or some other reaction will occur depends upon interactions among experiential, situational and other variables that are not well understood.…”
Section: Introductionmentioning
confidence: 96%